2016
DOI: 10.18632/oncotarget.11037
|View full text |Cite
|
Sign up to set email alerts
|

Clock gene Per2 as a controller of liver carcinogenesis

Abstract: Environmental disruption of molecular clocks promoted liver carcinogenesis and accelerated cancer progression in rodents. We investigated the specific role of clock gene Period 2 (Per2) for liver carcinogenesis and clock-controlled cellular proliferation, genomic instability and inflammation. We assessed liver histopathology, and determined molecular and physiology circadian patterns in mice on chronic diethylnitrosamine (DEN) exposure according to constitutive Per2 mutation. First, we found that Per2m/m liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 41 publications
5
54
2
2
Order By: Relevance
“…In support of human studies, experimental work in rodents documented accelerated tumor growth when mice, engrafted with lung adenocarcinoma or Glasgow osteosarcoma, were exposed to repeated jet lag conditions [9,10]. Similarly, enhanced tumor development has been described in mice with genetic disruption of the circadian clock (although this is not the case for all clock gene mutants) [9,[11][12][13] or surgical lesion of the central clock [14]. Taken together, circadian disruption coincides with increased carcinogenesis and faster tumor growth in a wide range of experimental setups.…”
Section: Circadian Clock Disruption Is Associated With Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…In support of human studies, experimental work in rodents documented accelerated tumor growth when mice, engrafted with lung adenocarcinoma or Glasgow osteosarcoma, were exposed to repeated jet lag conditions [9,10]. Similarly, enhanced tumor development has been described in mice with genetic disruption of the circadian clock (although this is not the case for all clock gene mutants) [9,[11][12][13] or surgical lesion of the central clock [14]. Taken together, circadian disruption coincides with increased carcinogenesis and faster tumor growth in a wide range of experimental setups.…”
Section: Circadian Clock Disruption Is Associated With Cancermentioning
confidence: 91%
“…This is a question worth asking, given the circadian regulation of physiological systems relevant to cancer (e.g., immune responses, cell cycle, DNA repair), and the effects of circadian disruption on tumorigenesis (see the first two sections). Indeed, host circadian rhythms have often been found to be disrupted in cancer patients and mouse cancer models [10,12,15,17]. For example, in mice with lung adenocarcinoma, circadian gene expression was largely affected in the liver, with many genes losing rhythmicity, others becoming rhythmic, and some being shifted earlier or later [15].…”
Section: Targeting the Clock In Tumors?mentioning
confidence: 99%
“…Mteyrek assessed liver histopathology, and determined molecular and physiology circadian patterns in mice on chronic diethylnitrosamine exposure, according to constitutive PER2 mutation [34]; PER2 mutation severely deregulated liver gene or protein expressions related to three cancer endpoints, including uncontrolled proliferation, genomic instability, and tumor promoting inflammation, and accelerated liver carcinogenesis several-fold [34]. Previously, it was demonstrated that mutation or knockout of clock genes PER2, CRY1/CRY2 or BMAL1 also accelerated the development of lymphomas following whole body exposure to γ radiations [35,36].…”
Section: Clock-work Dysfunction and Cancermentioning
confidence: 99%
“…Per2 mutation accelerates hepatocarcinogenesis through uncontrolled proliferation, genomic instability and tumor promoting inflammation. This mutation increases HCC several folds without any significant effect on CCA development …”
mentioning
confidence: 97%
“…Circadian disruption induced by Per2 mutation, constant light or chronic jet lag exposure has been shown to promote DEN‐induced liver carcinogenesis, resulting in increased formation of a majority of HCC and few CCA in rats and mice . DEN is usually used for liver cancer initiation (2–4 weeks of DEN exposure) and induces the formation of dysplastic foci with altered hepatocytes.…”
mentioning
confidence: 99%